Isolated Lymphoid Follicles are Dynamic Reservoirs for the Induction of Intestinal IgA - Knoop, Kathryn A.; Newberry, Rodney D. (Frontiers in Immunology, 2012)
IgA is one of the most important molecules in the regulation of intestinal homeostasis. Peyer’s patches have been traditionally recognized as sites for the induction of intestinal IgA responses, however more recent studies demonstrate that Isolated Lymphoid Follicles (ILFs) can perform this function as well. ILF development is dynamic, changing in response to the luminal microbial burden, suggesting that ILFs play an important role providing an expandable reservoir of compensatory IgA inductive sites. However, in situations of immune dysfunction, ILFs can over-develop in response to uncontrollable enteric flora, resulting in ILF hyperplasia. The ability of ILFs to expand and respond to help control the enteric flora makes this dynamic reservoir an important arm of IgA inductive sites in intestinal immunity.